Manual Remodelling of AF4 and O2 Electrodes in Schizophrenia - Redi Gunawan; Indah Nursuprianah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
Manual recreation of AF4 and O2 electrodes in schizophrenia. This study aims to: a) Know the EEG signals in the brain in humans, b) find out how manual rearrangements of the AF4 electrode and O2 electrode in schizophrenic patients and c) find out how the interpolation method compares at the AF4 and O2 electrodes in schizophrenic patients.Rearrangement of AF4 and O2 electrode manuals in schizophrenic patients, there are various ways, namely (a) graph of results of analysis, (b) enlarge graph, (c) create intervals and intersection points, (d) fitting in matlab and (e) analysis.There is a difference between the interpolation method of Newton degree 4th polynomial with the Lagrange degree 4th polynomial interpolation method which is the percent error by using Newton degree 4th when the graph is at the beginning until it is at the top is still stable with the mean value of error 14.118 % as well as the polynomial error with using Lagrange degree 4 is much better than Newton's 4th order with an average percent error of 4.69 %. While there is an equation between Newton degree 1 interpolation method with interpolation method of Lagrange degree 1 polynomial on electrode O2 value of error 0%